Workshop for the revision of Ecosystem Overviews of the Baltic Sea Ecoregion (WKBALEO) - Ammar, Yosr; Belgrano, Andrea; Bergström, Lena; Całkiewicz, Joanna; Drgas,Aleksander; Faithfull, Carolyn; Gorokova, Elena; Gruduls, Janis; Ito, Maysa; Jurgensone, Iveta; Juva, Katriina; Labuce, Astra; et al. (ICES SCIENTIFIC REPORTS, 2024)
Workshop for the revision of the Ecosystem Overview of the Baltic Sea Ecoregion (WKBALEO) worked to synthesize the knowledge that underpins the revision of the ICES Baltic Sea Ecosystem Overview. The Baltic Sea Ecosystem Overview aims to determine the main human activity sectors that cause pressures impacting the ecosystem components. WKBALEO experts have evaluated the links between sectors, pressures and ecosystem components using a linkage framework and pressure assessment process that examines and scores all direct pressures and human activities for the Baltic Sea ecoregion following the ICES technical guidelines methodology and using the most up-to-date scientific knowledge. The results indicate that most prevalent pressures in the Baltic Sea are related to nutrient discharge from multiple sources as well as impacts from species extraction, e.g. fishery including bycatch and substrate disturbance. Furthermore, contaminants and litter, mainly due to their persistence and widespread prevalence, were identified as significant pressures in the Baltic Sea. This report also includes a description of the current ecosystem state in the Baltic Sea, where large areas of low oxygen concentration in the Central Baltic affecting benthic productivity, internal nutrient cycling, and fish recruitment, are especially concerning. Despite extensive literature on the Baltic Sea there are still knowledge gaps on the cumulative effects of pressures on ecosystem components, particularly for contaminants and their sources. The workshop discussed emerging issues such as the increased requirement for offshore wind farms and mining, which can have impacts on the ecosystem as well as on management decisions in the future.
Keywords: ecosystem overview; pressure assessment; linkage framework; Baltic Sea; human activites